Cash Management in Response to COVID-19 Pandemic at Regional Financial and Asset Management Agency of West Nusa Tenggara - Akhmadi, Muhammad Heru; Aldimasqi, Lalu Muhammad (Research Center and Case Clearing House PPM School of Management, 2024)
This study aims to explore regional treasury management in the face of the COVID-19 pandemic. This research uses qualitative methods through library research and field research to manage cash availability, optimization, and control at the Regional Financial and Asset Management Agency in West Nusa Tenggara Province. Data analysis uses the Atlas.ti application to get codes, categories, and network diagrams. The result shows that effective and efficient cash management is closely related to the presence of a cash management system. Several internal and external constraints challenge the Government in managing cash. The COVID-19 pandemic is one of the external obstacles that has become the Government's primary concern over the past three years. The Government has maintained financial system stability through responsive and adaptive management of the state budget through a cash management system that can retain cash availability and optimize state/regional cash. Maintaining cash management performance during force majeure conditions, such as during COVID-19, is essential in maintaining the availability of state/regional cash to finance government spending.